Dedifferentiated endometrioid carcinoma of the uterus : report of four cases and review of literature. Issue 1 (December 2017) - Han, Jiheun; Ki, Eun; Rha, Sung; Hur, SooYoung; Lee, Ahwon
Abstract Background Dedifferentiated endometrioid adenocarcinoma (DEAC) is rare and is known to be more aggressive than high-grade endometrioid carcinoma. Differentiating between the two is important to provide appropriate treatment for patients. Case presentation This is a retrospective study including four cases of DEAC of the uterus, which was diagnosed and treated in our Obstetrics and Gynecology department between January 2013 and December 2015. Clinical, pathological, and immunohistochemical staining features are discussed. Each tumor was composed of undifferentiated carcinoma (UC) and low-grade endometrioid carcinoma with abrupt transition between them. Two patients showed recurrence or progression within one month postoperatively and died at the last follow-up. An immunohistochemical study showed PAX-8, ER, PR, and E-cadherin expression in UC component. Conclusions DEAC should not be underdiagnosed as conventional endometrioid adenocarcinoma due to its fulminant clinical course. Therefore, UC, including DEAC, should be further categorized to provide intensive treatment to improve patient survival.